Multi-objective design optimization of industrial pump inducer to avoid cavitation instabilities. Issue 1 (1st April 2022) - Masuda, Itsuki; Takao, Shunya; Nakamura, Yushi; Miyabe, Masahiro
Abstract: In this paper, important four design parameters which are sweep radius, sweep angle, solidity and incidence angle were firstly extracted for the inducer shape optimization. A multi-objective optimization method was applied to the inducer and optimal design was manufactured by 3D-Printer. Pump performance tests and cavitation performance test were conducted for both baseline inducer and optimal one. In addition, internal flow at the inlet of the inducer was measured by PIV in order to investigate the onset and the scale of backflow. As the result, it was confirmed that the cavitation performance of the optimized inducer was improved by about 23% while maintaining pump efficiency. It was also clarified that the onset of backflow at partial flow rate was shifted to lower flow rate by PIV. Furthermore, the occurrence range of cavitation surge in the partial flow rate was narrowed. Based on the sensitivity analysis result, it was found that the influence of sweep radius on both cavitation performance and backflow onset was large. Moreover, some design guidelines are suggested in conclusion.